1998
DOI: 10.1016/s0378-1097(98)00250-x
|View full text |Cite
|
Sign up to set email alerts
|

Functional replacement of OprJ by OprM in the MexCD-OprJ multidrug efflux system of Pseudomonas aeruginosa

Abstract: For characterization of the MexCD‐OprJ efflux system of Pseudomonas aeruginosa involved in resistance to fluoroquinolones and the fourth‐generation cephems, we constructed mexC, mexD or oprJ mutants from the nfxB‐type PAO strains by insertion mutagenesis. The gene products in the resultant mutants were examined by immunoblot assay using murine and rabbit antibodies developed against purified protein and synthetic oligopeptides. Susceptibility of the mexC (MexC− MexD− OprJ−) and mexD (MexC+ MexD− OprJ−) mutants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 10 publications
2
31
1
Order By: Relevance
“…We cannot exclude the possibility that other outer membrane component(s) among the four remaining candidates is (are) important for function of the RND-type efflux transporters in V. cholerae. It has been reported in P. aeruginosa that several outer membrane components are present, and certain RND-type efflux transporters can utilize multiple outer membrane components (16,23,27,40). In order to understand the mechanism of drug transport via the RND-type efflux transporters, investigation of the interaction between the inner membrane component of the RND-type efflux transporter and the outer membrane component would be important.…”
Section: Discussionmentioning
confidence: 99%
“…We cannot exclude the possibility that other outer membrane component(s) among the four remaining candidates is (are) important for function of the RND-type efflux transporters in V. cholerae. It has been reported in P. aeruginosa that several outer membrane components are present, and certain RND-type efflux transporters can utilize multiple outer membrane components (16,23,27,40). In order to understand the mechanism of drug transport via the RND-type efflux transporters, investigation of the interaction between the inner membrane component of the RND-type efflux transporter and the outer membrane component would be important.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to MexAB-OprM, MexCD-OprJ and MexEF-OprN do not confer resistance to ␤-lactam antibiotics (65,115). Subunit swapping experiments demonstrated that the inner membrane efflux components of the MexAB-OprM transporter are responsible for the ␤-lactam specificity of the multidrug efflux pumps in P. aeruginosa (66,155,240). Recently, two new genes mediating resistance to quinolones, aminoglycosides, and macrolide antibiotics were cloned from the chromosome of P. aeruginosa (6,158).…”
Section: Resistance-nodulation-cell Division Familymentioning
confidence: 99%
“…This specificity for hydrophilic quinolones was also observed for PmrA and NorM (63,163). However, EmrB and VceB confer resistance only to hydrophobic quinolones, whereas LmrA and the multidrug transporters of the RND family transport both hydrophilic and hydrophobic quinolones (37,66,135,158,200,205). In addition to conferring resistance, the overexpression of multidrug transporters can also cause increased drug sensitivity.…”
Section: Antibiotic Resistancementioning
confidence: 99%
“…In this vein, it is worth noting that pumps of the RND-MFP-OMF type show considerable flexibility in regard to the OMF component that can be used in assembling a functional tripartite efflux system. Studies of artificially created hybrid multidrug efflux systems in P. aeruginosa have confirmed, for example, that OprM can replace the OprJ (19,74) and OprN (46) OMF components of the MexCD-OprJ and MexEF-OprN efflux systems, respectively. Similarly, OprJ can replace the OprM component of MexAB-OprM (74), and the E. coli OMF TolC can replace OprJ (73).…”
Section: Discussionmentioning
confidence: 97%